Case Report: Spontaneous acute hemopericardium - Chacón-Diaz, Manuel (Frontiers in Cardiovascular Medicine, 2024)
Acute hemopericardium is generally produced by complications of interventional procedures or traumatisms to the chest wall. In absence of those antecedents, clinicians face an arduous process of etiological diagnosis and treatment. We present the case of a male patient with history of Hodgkin´s lymphoma and aortic endovascular treatment years ago, who develop an episode of fever, chest pain and dyspnea that was complicated with cardiac tamponade diagnosed with echocardiogram and angio-tomography. In the operating room hemopericardium was diagnosed and drained with resolution of symptoms. Diagnosis work out was carried out with suspicion of tuberculous or neoplastic pericarditis with negative results. Patient was discharged with the diagnoses of viral or idiopathic pericarditis. The case highlights the use of multimodality images and laboratories procedures to lead to a correct diagnoses and treatment.